EFFORTS TO ENHANCE EXCELLENT HUMAN RESOURCES TOWARDS GOLDEN INDONESIA 2045 - K.P. Suharyono S. Hadiningrat; Verry Albert Jekson Mardame Silalahi (JIPOWER : Journal of Intellectual Power, 2024)
Indonesia Emas 2045 is a strategic vision that aims to make Indonesia a developed country, with one of the main focuses being the development of excellent Human Resources (HR). Global challenges such as the Industrial Revolution 4.0, technological disruption, demographic changes, and the need for new skills make improving the quality of human resources a national priority. Excellent human resources, who master technical skills such as artificial intelligence (AI), robotics, and the Internet of Things (IoT), as well as soft skills such as adaptability and creativity, are needed to improve Indonesia's competitiveness in the global market. This research aims to explore strategies for developing superior human resources through improving the quality of education, vocational training, and mastery of digital technology, and analyze the collaboration between the government, private sector, and educational institutions. This research uses a descriptive qualitative method based on literature study. The benefits of this research are to provide insights into the strategic steps that can be taken to bridge the skills gap between education and industry, and to provide recommendations for strengthening vocational education and cross-sector collaboration. In conclusion, developing superior human resources requires a holistic approach that includes improving access to quality education, competency-based training and mastery of modern technology. Strong collaboration between the government, businesses and educational institutions is key to achieving this vision. Recommendations include strengthening curricula relevant to industry needs, improving access to technology in remote areas, and expanding vocational training programs to prepare a globally competitive workforce by 2045.